HUBUNGAN PEMINATAN SISWA DENGAN PRESTASI AKADEMIK SISWA KELAS X SMA WACHID HASYIM 5 SURABAYA - Zahra, Sayyidah Fatimatuz; Mufidah, Elia Firda (Universitas Palangka Raya, 2023)
This research is to find out whether there is a relationship between student specialization and academic achievement of class X students at SMA Wachid Hasyim 5 Surabaya. This study used a sample of 30 students. The Pearson correlation value for the student interest variable is -0.163 and the sig. (2-tailed) value shows the number 0.391 which means it is greater or more than 0.05 as well as the Pearson correlation value on the academic achievement variable showing the number -0.163 and the sig.( 2-tailed) shows the number 0.391 which means more than the standard significance of 0.05 which means there is a significant negative correlation between the student's interest variable (X) and the student's academic achievement variable (Y). The students' specialization is at a very high level, as many as 24 students (80%), the rest are in the high category as many as 4 students (13%) and the moderate category as many as 2 students (7%). While the average academic achievement of students is in a very high level, as many as 22 students (73 %), the rest are in the high category as many as 8 students (27%).